Study the effect of different temperatures on the biofilm production in Proteus mirabilis isolated from urinary tract infection patients - Ali A. Ghazay; Abbas Mayar Hezam; Mohammed M. Alkhuzaie; Israa Salih Obayes (Al-Qadisiyah Journal of Pure Science, 2020)
15 isolates (39.4%) of Proteus mirabilis  were obtained from a total of 38  patients with urinary tract infections  in Al-Diwaniyah Teaching Hospital. All isolates were diagnosed with phenotypic, microscopic and biochemical tests. PCR technique was also used as a confirmatory test to investigate the 16S rRNA gene (product size 239bp) in Proteus mirabilis  , where the results showed the presence of the gene in all isolates .On the other hand ,the detection of biofilm formation   in Proteus mirabilis  isolated from patients urinary tract infection was done using the tubes method .The results showed that 10 (75%) isolates were capable of producing the biofilm, where the value of the optical density of the formed biofilm ranged from 0.064-0.411 nm.Then, the effect of diefferent temperatures (25,30 37,40) ℃ on the Biofilm Formation in Proteus mirabilis  was studied, Where the most efficient bacteria were selected in the production of the biofilm and the test was carried out .The results showed that the bacteria were unable to form the biofilm at 25℃ either  at 3040℃, the biofilm is very thin at 37℃ and 40℃, it becomes a thick biofilm.The results of the current study showed that the temperature has a significant effect on the production of the biofilm and that the thickness of the biofilm increases with increasing temperature